Potensi Kebangkrutan dan Pertumbuhan Perusahaan: Pengaruhnya Terhadap Penerimaan Opini Audit Going Concern pada Perusahaan Manufaktur - Christina Andriani Ayu Mahardika; Veny Anindya Puspitasari (The Indonesia Capital Market Institute, 2020)
Auditor's opinion is quite important information related to one's investment decisions. Going concern opinion will be useful for users of financial statements, especially investors as a negative sign about the survival of the company. This study aims to determine the effect of potential bankruptcy and company growth on the acceptance of going concern audit opinion in manufacturing companies. The logistic regression model was used to test the hypothesis in this study. From the results of data processing, it is obtained that the potential for bankruptcy affects the acceptance of going concern audit opinion in manufacturing companies. However, it turns out that the company's growth does not affect the acceptance of going concern audit opinion in manufacturing companies.